STRATEGI INTEGRASI SOSIAL WILAYAH TRANSMIGRAN MELALUI PUSTAKA MUSAMUS DI DISTRIK SOTA MERAUKE - Irhamni Rahman; Sokhivah; Clara Novita Anggraini (DEVELOPMENT: Journal of Community Engagement, 2026)
South Papua faces complex challenges to social cohesion due to the spatial segregation of settlements between Indigenous Papuan communities and transmigrant groups. This study aims to analyze the sociocultural integration strategies developed by Pustaka Musamus in Sota District, Merauke Regency. Studying employs a qualitative approach with a case study design. Data was collected through in-depth interviews with program managers, customary leaders, and parents, complemented by participant observation of program activities. Data were analyzed using interactive thematic analysis, with data validity ensured through source and method triangulation. The findings indicate that spatial segregation between Route A, predominantly inhabited by the Kanum and Marind-Anim communities, and Route B, predominantly inhabited by Javanese transmigrants, has the potential to reinforce social distance, prejudice, and intergroup conflict. Pustaka Musamus functions as an inclusive, neutral, and egalitarian Third Space through mentoring 125 children and adolescents, non-formal literacy education, theater activities, and ecosystem-based team building. Daily interaction and cross-group collaboration strengthen trust and social capital for harmony from an early age. This study confirms that community-based sociocultural integration is relevant for strengthening inclusive and peaceful community development in Indonesia's border regions, in line with Sustainable Development Goals 10 and 16.